An Evaluation of Groundwater Recharge Potential Using Remote Sensing and the GIS Methods - Rouhollah Adinehvand (مهندسی منابع آب, 2019)
Application of remote sensing and geographic information system to the preparation of thematic maps and their integration in the form of zoning maps provide an important tool for assessing the potential of groundwater recharge sites. Thematic maps using effective factors in recharge activities namely the hydrogeological factors such as spring discharge and structural factors such as joint and fractures; lithological factors such as formation type; topography such as slope, slope aspect and topographic wetness index; and climatological factors such as rainfall, temperature, and also land use were applied in preparation of the groundwater recharge potential map. Thematic maps were prepared using remote sensing and by a referring approach and pair-wise and applying an expert view and also by field observations. Every thematic map was weighted and rated with respect to its effect on recharge. Finally, differently weighted maps were rated to prepare groundwater recharge site map. To verify the relative accuracy of groundwater recharge potential map, discharge of springs in the study area was used. The results show that most of the catchment area of the large springs located in the areas of high recharge potential, indicating the relatively high accuracy of the above-mentioned method.